DESKRIPSI KETERAMPILAN KERJA ILMIAH SISWA PADA MATERI LAJU REAKSI DI KELAS XI - Suprianto, Bintang; Sahputra, Rachmat; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe students' scientific work skills on material of reaction rate in class XI of SMA Negeri 1 Sungai Ambawang. This research is a descriptive form with subjects 22 students. This study used the instruments in the form of identification sheets, observation sheets, and interview sheets. The processing of research data is done by assigning a score to the results of the work of students which then the score is accumulated to get the percentage of the category of students' abilities in doing scientific work. The results showed that the scientific work skills from class XI IPA 1 of SMA Negeri 1 Sungai Ambawang as a whole can be categorized quite well with the skilled category at the stage of conducting experiments (75%), quite skilled category at the stage of formulating problems (64.8%), formulating hypothesis (72.7%), analyzing data (65.9%), and the stages of making conclusions from experimental results (70.5%), as well as the less skilled category at the stage of formulating experimental variables (51.1%), formulating operational definitions of variables (31.8%), and at the stage of communicating data in the form of tables and graphs (38.6%).